Implications of alcoholic cirrhosis in atherosclerosis of autopsied patients - Silveira,Luciano Alves Matias da (2017)
Summary Introduction: Alcoholism is a major public health problem, which has a high social cost and affects many aspects of human activity. Liver disease is one of the first consequences of alcohol abuse, and steatosis, liver cirrhosis and hepatitis may occur. Other organs are also affected with pathological changes, such as pancreatitis, cardiomyopathies, dyslipidemias and atherosclerosis. Objective: To identify the occurrence and degree of atherosclerosis in alcohol-dependent individuals with liver cirrhosis, observing macroscopic and microscopic changes in lipid and collagen deposits and in the liver. We also aimed to verify the association of lipid and collagen fiber deposits with gender, age and body mass index, and to relate alcoholism, liver cirrhosis and atherosclerosis. Method: We performed a study based on autopsy reports of patients with alcoholic liver cirrhosis, with analysis of aorta and liver fragments to verify the occurrence and degree of atherosclerosis, as well as collagen contents. Results: Microscopic atherosclerosis was higher in young subjects (early injury) and in patients with alcoholic liver cirrhosis. The macroscopic analysis of atherosclerosis in aortas showed that patients in more advanced age groups presented more severe classifications. Atherosclerosis, both micro and macroscopically, and the percentage of fibrosis in the liver and aorta were more expressive in females. Conclusion: Cirrhotic patients presented a higher percentage of fibrosis and lipidosis, and may represent a group susceptible to the accelerated progression of cardiovascular diseases. Investigative studies contribute to targeting health-promoting interventions, reducing the mortality and costs of treating cardiovascular disease.